2011
DOI: 10.1007/s00221-011-2636-9
|View full text |Cite
|
Sign up to set email alerts
|

Local and global effects of neck muscle vibration during stabilization of upright standing

Abstract: Neck muscle vibration (NMV) during upright standing is known to induce forward leaning, which has been explained as a global response to the (illusory) perception of a lengthening of the dorsal neck muscles. However, the effects of NMV both at the level of individual joints and on whole-body postural coordination, and its potential modulation by vision, have not yet been analyzed in detail. Eight healthy young adult participants completed a total of ten trials each, with a 10-s period of unperturbed standing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Vibration was applied via a handheld vibration device (Vibrasens; Techno Concept, France) that was already used in previous studies [7]. Neck muscles were vibrated for 30 seconds with a frequency of 100 Hz [5] and a linear displacement of 1 mm of the vibration head.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibration was applied via a handheld vibration device (Vibrasens; Techno Concept, France) that was already used in previous studies [7]. Neck muscles were vibrated for 30 seconds with a frequency of 100 Hz [5] and a linear displacement of 1 mm of the vibration head.…”
Section: Interventionmentioning
confidence: 99%
“…More specifically, subjects showed increased body sway displacements toward the side opposite to the vibrated spot [6]. Furthermore, altered postural alignment in the upper cervical spine [7], a shifted perception of the body midline [8,9], and illusory movements have been reported [10]. These vibration-induced impairments are of short duration and depend on the length of application.…”
Section: Introductionmentioning
confidence: 99%
“…The processing of recorded signals from both the motion capture system and force plate was performed using MATLAB (MathWorks). The recorded signals (marker and COP displacements) were low-pass filtered with a zero phase, second-order Butterworth filter with a 10 Hz cutoff frequency because the frequency of body kinematic signals is Ͻ10 Hz during quiet standing (Winter, 1995;Sienko et al, 2010;Verrel et al, 2011). The two positions of each pair of homonymous markers (which were placed symmetrically on the aforementioned body landmarks) were averaged to generate a postural profile represented in the midsagittal plane.…”
Section: Methodsmentioning
confidence: 99%
“…Another recent study found that dorsal neck muscle vibration induced a posterior leaning of the head whereas all of the other body segments leaned in the anterior direction (Verrel et al, 2011). Thus, a coordinated multisegmental response to torso cu-taneous vibration may be likely.…”
Section: Introductionmentioning
confidence: 97%
“…Vibration of dorsal neck muscles stimulates neck proprioceptive inputs [8][9][10] , and changes proprioceptive signals code of body spatial orientation and postural stabilization 11) . An increase in forward leaning was induced by neck muscle vibration during static standing, which has been explained as a response to the perception of the lengthening of the dorsal neck muscles 12) .…”
Section: Introductionmentioning
confidence: 99%